2005
DOI: 10.3928/01484834-20050201-06
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions of Critical Thinking in Student Clinical Experiences

Abstract: Critical thinking is an essential skill for nurses who practice in complex health care systems. This study explored nursing faculty members' perceptions of teaching critical thinking to baccalaureate student nurses in clinical settings. Six clinical faculty members were interviewed using an ethnographic approach. Findings focus on two domain analyses that describe the nature of critical thinking and strategies to effectively teach it. Faculty members conceptualized critical thinking as “putting it all together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…Questionamento Auxiliar os participantes a resolver problemas e criar alternativas para lidar com problemas que os confrontem Simpson, Courtney (9) Hoffman (10) Profetto-Mcgrath, Bulmer, Day, Yonge (11) Magnussen, Ishida, Itano (12) Twibell, Ryan, Hermiz (13) Staib (6) Hoffman (10) Butts, Lundy (14) Tomey (15) Desanto-Madeya (16)…”
Section: Objetivo Características Autoresunclassified
See 1 more Smart Citation
“…Questionamento Auxiliar os participantes a resolver problemas e criar alternativas para lidar com problemas que os confrontem Simpson, Courtney (9) Hoffman (10) Profetto-Mcgrath, Bulmer, Day, Yonge (11) Magnussen, Ishida, Itano (12) Twibell, Ryan, Hermiz (13) Staib (6) Hoffman (10) Butts, Lundy (14) Tomey (15) Desanto-Madeya (16)…”
Section: Objetivo Características Autoresunclassified
“…A estratégia do questionamento requer dinamicidade durante o processo ensinoaprendizagem, além de um ambiente favorável à abertura que permita aos estudantes elaborarem questões sobre a temática de interesse. O questionamento, ainda, auxilia na resolução de problemas, além de estimular os participantes na procura de resultados e fornecer alternativas para lidar com problemas que os confrontem (12,13) .…”
Section: Aprendizagem Baseada Em Problemasunclassified
“…C ritical thinking is a valued and highly desired skill in nursing practice (Mundy & Denham, 2008;Twibell, Ryan, & Hermiz, 2005). Entry to practice competencies emphasize that RNs demonstrate critical thinking and critical inquiry to integrate new and ever-changing knowledge, as well as advances in technology, that affect nursing practice (Canadian Council of Registered Nurse Regulators, 2012).…”
mentioning
confidence: 99%
“…In addition, it was determined that as the student gained experience, self-confidence, and knowledge, understanding of the clinical picture and recognizing patterns to assist the student in anticipating patient needs were developed. Twibell, Ryan, and Hermiz (2005) explored perceptions of nursing faculty in teaching critical thinking. Faculty identified the core nature of critical thinking as "putting it all together through information seeking, reflecting, assigning meaning, problem solving, predicting, planning, and applying information" (Twibell, Ryan, & Hermiz, 2005, p. 71).…”
Section: Development Of Critical Thinkingmentioning
confidence: 99%
“…Regularly questioning students using the Socratic Method that challenges thinking and encourages explorations of differing or opposing points of view can enhance the development of critical thinking (Paul & Heaslip, 1995). Twibell et al (2005) suggested that critical thinking is best taught in clinical settings. Strategies for teaching critical thinking in the clinical environment, as identified by Twibell et al, include: questioning by instructors, written feedback on nursing care plans, clinical case studies, clinical conferences, and journaling.…”
Section: Development Of Critical Thinkingmentioning
confidence: 99%